The Influence of Nutritional Status on the Incidence of Postpartum Hemorrhage in Three Community Health Centers (CHCs) in Dili, Timor Leste - Alcinda Pinto Fernandes; Novida Ariani; Diadjeng Setya Wardani; Hermes Peguinho; Hadidja Binti Ali Hosman Maia; Filomena Soares; Mirioldis Matos Rodríguez (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Postpartum hemorrhage (PPH) remains a leading cause of maternal mortality in low- and middle-income countries, including Timor-Leste. This analytical cross-sectional study, conducted from January to December 2024 in three community health centers (CHCs) in Dili, examined the association between maternal nutritional status and the incidence of PPH. Nutritional indicators included pre-pregnancy body mass index (BMI), gestational weight gain, anemia status, and mid-upper arm circumference (MUAC). Data were collected from medical records of 130 postpartum mothers (65 with PPH, 65 without). The prevalence of PPH was 50%. Among participants, 22.1% had anemia (hemoglobin <11 g/dL), 50.8% had MUAC <23.5 cm, and 41.5% had a pre-pregnancy BMI outside the WHO normal range (18.5-24.9 kg/m²). Only 26.4% achieved gestational weight gain within Institute of Medicine guidelines. Logistic regression analysis revealed that anemia significantly increased the risk of PPH (OR = 3.4; 95% CI: 1.38-8.40; p = 0.011), while other nutritional indicators showed no significant association. These findings highlight the critical role of antenatal anemia screening and targeted nutritional interventions in reducing PPH risk. This study provides locally relevant evidence to inform maternal health strategies in Timor-Leste. Keywords: Postpartum hemorrhage, Pre-pregnancy BMI, weight gain, Mid-Upper Arm Circumference, Antenatal Care, Community health center